2019
DOI: 10.1177/1129729819874986
|View full text |Cite
|
Sign up to set email alerts
|

The electrocardiographic method for positioning the tip of central venous access device

Abstract: Background: The electrocardiogram-based insertion method is non-radiative, allowing real-time positioning verification and reducing the need for postoperative repositioning. Methods: Relevant databases published from January 1990 to January 2019 in PubMed, Web of Knowledge, Medline and Ovid’s database were searched, comparing the effectiveness of electrocardiogram-guided catheter tip positioning (electrocardiogram-guided group) and the landmarks-guided insertion plus chest X-ray confirmation (landmarks-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Obviously, it is mandatory to check the correct position of the tip in case of symptomatic patients or when there is a well-founded suspicion that something has happened and that the tip of the PICC is no longer in a safe position and therefore the vascular catheter must be repositioned correctly [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, it is mandatory to check the correct position of the tip in case of symptomatic patients or when there is a well-founded suspicion that something has happened and that the tip of the PICC is no longer in a safe position and therefore the vascular catheter must be repositioned correctly [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 A review by Yu and Yuan concluded that using the IC ECG method to place CVADs was more accurate compared to the anthropometric method (OR: 0.21, 95% CI: 0.14–0.34, p < 0.001) however the meta-analysis performed incorporated both randomised and non-randomised studies with significant heterogeneity and risk of selection bias. 31…”
Section: Discussionmentioning
confidence: 99%
“…30 A review by Yu and Yuan concluded that using the IC ECG method to place CVADs was more accurate compared to the anthropometric method (OR: 0.21, 95% CI: 0.14-0.34, p < 0.001) however the meta-analysis performed incorporated both randomised and non-randomised studies with significant heterogeneity and risk of selection bias. 31 Most studies assessing the effect of IC ECG have concentrated on homogenous populations such as neonates and paediatrics or those with cancer, and usually on specific devices (exclusively with PICCs or CICCs). [13][14][15]32 This includes a multicentre randomised trial in 1000 cancer patients across eight hospitals in China comparing IC ECG to anatomical landmark technique using PICCs from a single manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, repeating the CXR to confirm correct positioning increases both the dose of radiation exposure and the cost involved. 9 , 12 , 13 It is also not a feasible option in the theatre setting during the peri-operative period.…”
Section: Introductionmentioning
confidence: 99%